Kualitas Pelayanan Fiskus, Sanksi Perpajakan, Biaya Kepatuhan Wajib Pajak Dan Penerapan E-Filing Terhadap Kepatuhan Wajib Pajak Di Kp2kp Banjarnegara (Studi Empiris Pada Kp2kp Banjarnegara) - Eling Ri Kurniati; Faiz Rizqi (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2019)
ABSTRACT This research is specifically concern about problems regarding taxpayer compliance which form the preliminary survey result shows that taxpayer compliance in the KP2KP Banjarnegara is still low, especially the level of taxpayer compliance around 48.07%. The purpose of this study was to determine the effect of tax quality, authorities service, tax sanctions, taxpayer compliance costs, and the application of e-filing on tax compliance in the KP2KP Banjarnegara. This research obtained 100 respondents as sample with simple random sampling. Data collection techniques were carried out by questionnaire. The data analysis technique used multiple linear regression analysis. The hypothesis results obtained that the service quality of tax authorities had a positive and significant effect on taxpayer compliance, taxation sanctions had a negative and no significant effect on taxpayer compliance, taxpayer compliance costs had a positive and significant effect on taxpayer compliance and the application of e-filing had a negative and no significant effect for taxpayer compliance.